سوشل میڈیا پر اسلاموفوبیا کے خلاف چیلنجز: ایک علمی جائزہ: An analytical review of Challenges against Islamophobia on social media - Fakhr ud-din, Dr. Muhammad; Khan, Hafiz Ullah (Al-Amīr Research Journal for Islamic Studies, 2023)
This research article describes the complex relationship between combating on social media and maintaining a delicate balance between freedom of expression and blasphemous content. Given the increasing Islamophobic incidents online, this study uses a multidisciplinary approach, drawing on sociology, studies to those countering discriminatory narratives against Islam. You can the challenges they face. Explores how freedom of expression, a fundamental aspect of, can unintentionally contribute to Islamophobic discourse and the struggle to find a balance between divisive and responsible content. Additionally, the article the role of social media platforms in reducing Islamophobia, evaluating their policies, algorithms, and community guidelines. It evaluates the effectiveness of existing measures to prevent hate speech while maintaining the principles of freedom of expression. By examining legitimate criticism and its potential misuse to stifle this study also sheds light on the concept of blasphemy. Real-world examples the line between expressing dissent and entering offensive territory. Ultimately, the article provides information on strategies to combat Islamophobia on social compromising freedom of expression. It promotes a nuanced understanding of the challenges and offers recommendations for individuals, communities, and social media platforms to foster an environment that fosters respectful dialogue while addressing discrimination. Keywords: Islamophobia, social media, freedom of expression, blasphemy, religious discrimination.